Knowledge about Epilepsy and Attitudes toward Students with Epilepsy among Middle and High School Teachers in Kuwait - Eman Al-Hashemi; Abdullatif Ashkanani; Haneen Al-Qattan; Asmaa Mahmoud; Majd Al-Kabbani; Abdulaziz Al-Juhaidli; Ahmad Jaafar; Zahraa Al-Hashemi (International Journal of Pediatrics)
Background and Objectives. Attitudes toward students with epilepsy and epilepsy-related knowledge of teachers are crucial for child’s safety in the school. The aim of this study was to evaluate teachers’ knowledge and attitudes toward epilepsy. Methods. This cross-sectional study included 824 teachers from 24 randomly selected middle and high schools. Scale of Attitudes Toward Persons with Epilepsy (ATPE) was modified to assess teachers’ knowledge about epilepsy and attitudes toward students with epilepsy. Results. Median knowledge score about epilepsy was 5 (out of 13), while median attitude score was 10 (out of 15). Both knowledge and attitude median scores were significantly higher in senior teachers with longer teaching experience and in respondents who dealt with a person with epilepsy. There was significant association between knowledge score and attitude score (p<0.01). Logistic regression showed that significant variables, independently associated with poor knowledge after adjusting for possible confounders, were not having a family member with epilepsy (p=0.009), unawareness of life circumstances of persons with epilepsy (p=0.048), and a poor attitude score (p<0.001). Conclusion. School teachers in Kuwait have relatively poor knowledge about epilepsy but have positive attitudes toward students with epilepsy. A number of historical and stigmatizing ideas about epilepsy still exist. It is recommended to provide teachers with information about handling seizures in the educational setting through development and implementation of epilepsy education programs.